2021
DOI: 10.3389/fpls.2021.647507
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Long-Lived Albino Epipremnum aureum ‘Golden Pothos’ and Restoring Chloroplast Development

Abstract: Chloroplasts are organelles responsible for chlorophyll biosynthesis, photosynthesis, and biosynthesis of many metabolites, which are one of key targets for crop improvement. Elucidating and engineering genes involved in chloroplast development are important approaches for studying chloroplast functions as well as developing new crops. In this study, we report a long-lived albino mutant derived from a popular ornamental plant Epipremnum aureum ‘Golden Pothos’ which could be used as a model for analyzing the fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 82 publications
(154 reference statements)
1
4
0
Order By: Relevance
“…On the other hand, by spraying the antioxidant bilirubin at the same concentration, photo plants became more resistant to absorbing formaldehyde. The results of this study were also confirmed through other similar studies (Hung et al, 2021).…”
Section: Indoor Plantssupporting
confidence: 91%
“…On the other hand, by spraying the antioxidant bilirubin at the same concentration, photo plants became more resistant to absorbing formaldehyde. The results of this study were also confirmed through other similar studies (Hung et al, 2021).…”
Section: Indoor Plantssupporting
confidence: 91%
“…In this context, albino plants are also commonly used for studying chloroplast development and function. Previous studies show that albino plants derived from mutation together with their green counterparts are ideal genetic materials for identifying mutated genes involved in the chloroplast biogenesis and development (Hung et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Chlorophyll biosynthesis is a complex biological process catalyzed by at least 17 different key enzymes, and a variety of cofactors and transcription factors participate in this process. Numerous chlorophyll-deficient maize mutants have been identified, such as l*-Blandy 4 , oro , oro2 , and cf1 ( Huang et al, 2009 ; Hung et al, 2021 ). Although the function of MgPEC in chlorophyll biosynthesis has been confirmed to catalyze the conversion of MgPME to DV Pchlide, its entire structure and components are not clear.…”
Section: Discussionmentioning
confidence: 99%
“…EMS-mutagenized cucumber mutants have pale green leaves and fruits controlled by a recessive allele of CsYcf54 that encodes a Ycf54-like protein required for MgPEC ( Lun et al, 2016 ). Epipremnum aureum mutants exhibit a chlorophyll-deficient phenotype controlled by the nuclear gene EaZIP that is a homologous gene of Arabidopsis CHL27 and tobacco NTZIP , and AtCHL27 can restore its green phenotype and chloroplast development ( Hung et al, 2010 , 2021 ).…”
Section: Introductionmentioning
confidence: 99%